Exploring Financial Approaches to Evaluate Commercial Bank Profitability: An Empirical Analysis on Capital Adequacy Ratio, Loan Deposit Ratio and Non-Performing Loans - Jenia Nur Soelistyoningrum; Marita Marcelya; Novinda Krisna Putri (Soegijapranata Catholic University, 2023)
Banking is a high-risk industry since it is responsible for managing public assets and investing them in securities or loans. As a result, assessing commercial bank performance is critical for understanding their health and efficiency. A financial approach is used to assess credit risk, liquidity, and bank adequacy in accordance to the requirements of Financial Service Authority (OJK). This research aims to determine the impact of the Capital Adequacy Ratio (CAR), Loan Deposit Ratio (LDR), and Non-Performing Loans (NPL) on bank’s performance in 2017-2019. Using the purposive sampling technique, the final sample consists of 114 observations-sample. A multiple linear regression analysis was adopted on balanced panel data using the secondary data from commercial banking sector in Indonesia Stock Exchange. Chow test and Hausman test were used to finalize the findings which is to ensure that the right model to be used for the analysis. The findings demonstrate that CAR, LDR, and NPL simultaneously impact significantly the performance. However, partially only CAR and NPL show impact on the performance whilst LDR does not. The study provides implications for bank managers in managing capital and loan portfolios. It also contributes to the existing literature on bank performance.